2022
DOI: 10.3389/fcimb.2022.964290
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of K1 ST23 and K2 ST65 hypervirulent klebsiella pneumoniae as true pathogens with specific virulence genes in cryptogenic pyogenic liver abscesses Shiraz Iran

Abstract: Hypervirulent Klebsiella pneumoniae (hvKp) pathotype is emerging worldwide in pyogenic liver abscesses (PLAs). However, the role of virulence factors in pathogenicity remains unclear. On the other hand, the epidemiology of PLAs in Iran is unknown. From July 2020 to April 2022, bacterial species were isolated and identified from the drainage samples of 54 patients with PLAs. K. pneumoniae as the most common pathogen of pyogenic liver abscesses was identified in 20 (37%) of the 54 patients. We analyzed the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…K1 and K2 were strongly associated with high virulence in the previous study, and our results also found that K1 and K2 showed lower drug resistance ( Lee et al, 2017 ; Sohrabi et al, 2022 ). In our study, T6SS-positive strains had a higher detection rate of the K1 capsular serotype than T6SS-negative strains.…”
Section: Discussionsupporting
confidence: 86%
“…K1 and K2 were strongly associated with high virulence in the previous study, and our results also found that K1 and K2 showed lower drug resistance ( Lee et al, 2017 ; Sohrabi et al, 2022 ). In our study, T6SS-positive strains had a higher detection rate of the K1 capsular serotype than T6SS-negative strains.…”
Section: Discussionsupporting
confidence: 86%
“…Identi cation of virulence-associated genes. Four genes for virulence including iucA, iroB, plasmid-borne rmpA and an isoform rmpA2 were identi ed by PCR with the speci c primers previously reported [25][36] [30] (Table 1). Characterization of capsular types.…”
Section: Methodsmentioning
confidence: 99%
“…[4] In addition, virulence factors in Klebsiella pneumoniae, capsular serotype, mucoviscosity-associated gene A (magA), rmpA and aerobactin are important in the formation of liver abscesses. [4,5] Klebsiella pneumoniae strains expressing the capsular type K1 or K2 antigen are virulent. These serotypes have a high prevalence of resistance to phagocytosis and intracellular killing by neutrophils and bactericidal complements in a patient's serum.…”
Section: Introductionmentioning
confidence: 99%
“…Although Klebsiella pneumoniae serotypes K1 and K2 isolated from patients with liver abscesses usually show hypermucoviscosity, they are known to be an indicator of capsular polysaccharide expression, which is related to resistance to phagocytosis. [5] magA has been identified as the gene that causes Klebsiella pneumoniae liver abscess and septic metastatic complications. [6] RmpA aids in capsule synthesis in addition to magA and capsular serotype K1/ K2.…”
Section: Introductionmentioning
confidence: 99%